Removal of micropollutants from wastewater combining adsorption and electrochemical regeneration - Pizzagalli, Giulia (Cranfield University, 2017)
Increasingly stringent legislations, such as the Water Framework Directive (WFD) and its daughter Directive on Environmental Quality Standards (EQS), have carried important implications for European policy on pollution control for water resources. EQS have been set or proposed for substances which hitherto had not been subjected to monitoring, calling for compliance assessments and new control measures. To address this challenge, the UK Water Industry Research (UKWIR) financed a Chemicals Investigation Programme (CIP), assessing the source, occurrence and removal of emerging pollutants in the final effluents of wastewater treatment works (WwTWs). A second phase of work, CIP2, now aims to create a justifiable base for future regulatory measures needed to achieve good status (i.e. compliance limits for specific substances), together with a data set on micropollutants’ concentrations from trials conducted at pilot and full scale all over the UK. As part of CIP2, the Arvia ODC (Organic Destruction Cell), a novel technology combining adsorption and electrochemical oxidation, has been investigated at pilot scale. Its overall performance was assessed by evaluating the removal of 68 emerging pollutants and priority substances (pharmaceuticals, steroids, industrial chemicals and heavy metals), by appraising its economic and environmental costs and by weighting its reliability, easiness of maintenance and operation. Overall, the unit was able to target pharmaceuticals better than any other class of substances, with removals consistently over 50% for the majority of them, being especially effective towards macrolide antibiotics (~ 60-70%) and statins (~70-80%). The majority of determinands (72%) were found to be at concentrations below the set EQS at discharge. However, despite some evidence of promising performance, the ODC appeared to promote the accumulation of metals (i.e. zinc, nickel) in the final effluent and overall showed quite a weak performance in relation to sanitary determinands. A multi criteria analysis was performed to compare the ODC to alternative tertiary treatments. Although considerably lower than alternative treatment technologies (i.e. GAC or ozonation), energy consumption, normalised at 0.14 kWh/treated m³, represented the major contributing factor to estimated OPEX (1.1 pence/kWh), steadily increasing with population served. The ODC does not require chemical dosing, thus lessening the sludge production and potentially offering lower operational carbon usage than other advanced oxidation processes. Further testing of the technology was carried on at bench scale, in order to assess the unit’s performance in more controlled circumstances (spiked tap water). The trial allowed to single out the main parameters (mainly current density and effluent flow) responsible for the ODC performance and to evaluate to what extent their variation contributed to the removal of carbamazepine, a pharmaceutical compound whose persistence and toxicity in the aquatic environment determined its inclusion in the list of substances investigated in CIP2. The best removal performance (78%) was achieved at intermediate values for the ranges of flow and current density explored (5 L/h, 4 mA/cm²), seemingly allowing a synergic contribution of both adsorption and electrochemical oxidation. Although the technology has been proved to perform satisfactorily towards specific micropollutants in both trials, it is not applicable with the same degree of success to the removal of the wide range of chemicals investigated in CIP2. Moreover, due to its relative novelty and hitherto lack of full scale applications, the technology still requires stages of development, especially in terms of hydraulics within the unit (i.e. backwash system) and upstream solids capture.
Keywords: Micropollutants; priority substances; Chemicals Investigation Programme; adsorption; electrochemical oxidation; ozonation